HUBUNGAN LITERASI KEUANGAN TERHADAP KEPUTUSAN BELANJA MAHASISWA - Sofiyanti, Vina; Hafid, Radia; Mahmud, Melizubaida (LP2M Institut Teknologi dan Bisnis Asia Malang, 2022)
This study aims to measure the relationship between Financial Literacy and Shopping Decisions of Economic Education Students, Class of 2018, Universitas Negeri Gorontalo. This study uses a quantitative approach, with 63 respondents (students) in Economics Education, class 2018. The main instrument is a questionnaire. The data collected are analyzed and tested with a simple linear correlation using the SPPSS 2022. The study result shows a relationship between financial literacy and shopping decisions of economic education students, class 2018, of 0,594 at the point of the correlation coefficient of 0,40 -0,599, which means it has a moderate or relatively strong relationship.